(untitled) (TERRA LATINOAMERICANA, 2024)
Biological nitrogen fixation (BNF) is a natural process that can supply up to 90% of nitrogen needed for some legumes, thus it represents a sustainable option to reduce the adverse ef fects of chemical fertilizers in agriculture. To evaluate the BNF ef ficiency of five bush bean cultivars, five bean cultivars of climbing habits and 10 wild bean populations, seedlings were inoculated with a composite of three strains of Rhizobium spp. A completely randomized design with five replicates was used and eight quantitative variables were recorded. Analyses of variance were performed, nodulation and nitrogen fixation ef ficiency indices were obtained, and principal component analyses (CP) were conducted. The analyses of variance and the nodulation and fixation ef ficiency indices showed dif ferences between genotypes. Peruano 16, Cuarenteño and Pinto Saltillo bush habit varieties were ef ficient in nodulation and nitrogen fixation. The wild populations ROL 633 and ROL 486 were ef ficient in nodulation and showed low ef ficiency in fixation. The orthogonal contrasts of the variables number and dry weight of nodules, total nitrogen and chlorophyll content, and nodulation and nitrogen fixation ef ficiency indices both by groups of genotypes, allow us to af firm that varieties of bush bean showed an outstanding behavior, overall surpassing the cultivated varieties of climbing habit and the wild genotypes. CP1 separated genotypes by stem and root length and CP2 by number and dry weight of nodules. The results confirm variability among bean genotypes in BNF, the existence of bush habit cultivars ef ficient in nodulation and fixation, and that there is potential for selection of ef ficient bean genotypes in BNF.